Tratti binari e tratti monovalenti nella rappresentazione delle vocali - Laura Bafile (Annali Online dell'Università di Ferrara. Sezione Lettere)
The paper deals with the nature of segmental primitives. Although the conception of features as binary units has dominated phonological literature for decades, it has been challenged in convincing ways by the alternative theory according to which primitives are monovalent units. The paper compares the two aforementioned approaches by focusing on the representation of vowels. I will argue in favour of the unarist conception through a discussion of data concerning vowel harmony and metaphony in Italo-Romance varieties